Women in culture an intersectional anthology for gender and women's studies - Scott, Bonnie Kime 1944-; Cayleff, Susan E.; Donadey, Anne; Lara, Irene (John Wiley & Sons, 2017)
"The thoroughly revised Women in Culture 2/e explores the intersections of gender, race, sexuality, gender identity, and spirituality from the perspectives of diverse global locations. Its strong humanities content, including illustrations and creative writing, uniquely embraces the creative aspects of the field" -- Provided by publisher.